Evolocumab Effectively Lowers LDL-C, Decreases Cardiovascular Outcomes in OSLER - Spevak, Aimee (MD Conference Express, 2015)
The OSLER extension studies randomized patients to receive standard of care or standard of care plus evolocumab. At 1 year, evolocumab lowered low-density lipoprotein cholesterol by 61% and demonstrated preliminary evidence that this may reduce the risk of cardiovascular events. Evolocumab was well tolerated across all gradients of achieved low-density lipoprotein cholesterol levels.